Micropetrosis – Occlusion of Osteocyte Lacunae - Kolibová, Sofie Dragoun; Busse, Björn; Jähn-Rickert, Katharina (Osteologie, 2022)
This article summarizes the current knowledge on micropetrosis – osteocyte lacunar occlusion, while focusing on the latest data on osteocyte viability and diabetic bone disease. The lacunae are fluid-filled ellipsoid spaces where osteocytes reside within the mineralized matrix. During osteocyte lifetime, the lacunar space is kept in a non-mineralized state. However, a dying osteocyte appears to enable the initiation of lacunar mineralization – creating a fossil within the living tissue. Elevated frequencies of micropetrosis are observed with advanced age, but also type 1 diabetes mellitus. The latter is a common health threat to our society with rising numbers of patients suffering from the disease associated symptoms including a secondary type of osteoporosis with an elevated risk of fragility fractures. While the underlying mechanism of diabetic bone disease is not entirely understood, more evidence is pointing towards a combinatory effect of loss of bone mass and an impaired overall bone quality. The high number of micropetrotic osteocyte lacunae leads to a more brittle bone tissue prone to microcracking. Further investigations are required to determine the implications of elevated micropetrosis as a reliable target of bone fragility.
Keywords: micropetrosis; osteocyte lacunar mineralization; osteocytes; diabetes mellitus; osteoporosis